2007
DOI: 10.1111/j.1365-2036.2007.03433.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to SS‐A/Ro‐52kD and centromere in autoimmune liver disease: a clue to diagnosis and prognosis of primary biliary cirrhosis

Abstract: SUMMARY BackgroundPrimary biliary cirrhosis (PBC) may be associated with various rheumatological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 25 publications
4
46
0
2
Order By: Relevance
“…Stinton et al 16) determined the prevalences of different autoantibodies among 109 patients with PBC (including 6 patients negative for AMA) using LIA (82% for AMA -M2, 73% for M2 -3E, 27% for anti -Sp100 antibody, 17% for anti -PML antibody, 27% for anti -gp210 antibody, 32% for anti -Ro -52 antibody and 11% for ACA), which were different from those observed in the present study (65% for AMA -M2, 77.5% for M2 -3E, 13.8% for anti -Sp100 antibody, 8.7% for anti -PML antibody, 40.0% for anti -gp210 antibody, 27.5% for anti -Ro -52 antibody and 32.5% for ACA). The reported prevalences of these autoantibodies vary among studies : 75 -96% for AMA -M2 17) , 57% for M2 -3E 18) , 20 -30% for anti -Sp100 antibody 17,19,20) , 19% for anti -PML antibody 21) , 17 -25% for antigp210 antibody 17,22) , 25 -28% for anti -Ro -52 antibody 23,24) , and 10 -30% for ACA 25 -27) . This variability may reflect differences in target populations, such as racial difference, timing of sample collection and other variables among institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stinton et al 16) determined the prevalences of different autoantibodies among 109 patients with PBC (including 6 patients negative for AMA) using LIA (82% for AMA -M2, 73% for M2 -3E, 27% for anti -Sp100 antibody, 17% for anti -PML antibody, 27% for anti -gp210 antibody, 32% for anti -Ro -52 antibody and 11% for ACA), which were different from those observed in the present study (65% for AMA -M2, 77.5% for M2 -3E, 13.8% for anti -Sp100 antibody, 8.7% for anti -PML antibody, 40.0% for anti -gp210 antibody, 27.5% for anti -Ro -52 antibody and 32.5% for ACA). The reported prevalences of these autoantibodies vary among studies : 75 -96% for AMA -M2 17) , 57% for M2 -3E 18) , 20 -30% for anti -Sp100 antibody 17,19,20) , 19% for anti -PML antibody 21) , 17 -25% for antigp210 antibody 17,22) , 25 -28% for anti -Ro -52 antibody 23,24) , and 10 -30% for ACA 25 -27) . This variability may reflect differences in target populations, such as racial difference, timing of sample collection and other variables among institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The anti -Ro -52 antibody is a type of anti -SS -A/Ro antibody that has been detected in many autoimmune diseases, including Sjogren's syndrome 36) . Granito et al reported that the population of PBC patients positive for anti -Ro -52 antibody includes significantly more patients with advanced histological stage and high serum bilirubin levels than dose the negative population 23) . In the present study, both the subset of patients positive for anti -gp210 antibody and that of patients positive for anti -Ro -52 antibody included significantly more patients with jaundice than did the subsets of patients negative for these antibodies, being consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…ANA is reported in 8%-77% of the PSC patients (Table 1). No particular ANA subspecificities seem to predominate; anti-dsDNA has been reported in 3%-29% [61,78,87,111] , anti-ENA in 4%-12% [78,111,112] , anti SSA/B in 1%-28% [78,87] and anti-RNP, anti-SCL70, anti-Sm and anti-ssDNA in a minority of patients [87] . SMAs have been reported in 0%-83% of PSC patients (Table 1) but the prevalence is also high in AIH, various malignancies and infections [107] .…”
Section: Antinuclear (Anas) and Smooth Muscle Antibodies (Smas)mentioning
confidence: 99%
“…The presence of anti-Ro52 antibodies has been reported in a wide variety of autoimmune diseases, particularly in myositis, scleroderma and autoimmune liver diseases [9,10], and have been associated with nonautoimmune diseases such as viral infections or neoplastic diseases [11].…”
Section: Introductionmentioning
confidence: 99%